Factors associated with incomplete adherence to integrase strand transfer inhibitor-containing single-tablet regimen among Japanese people living with HIV - Yusuke Kunimoto; Shinichi Hikasa; Masashi Ishihara; Mariko Tsukiji; Kazuko Nobori; Takeshi Kimura; Kenta Onishi; Yuuki Yamamoto; Kyohei Haruta; Yohei Kasiwabara; Kenji Fujii; Masahide Fukudo (BMC, 2024)
Abstract Background People living with human immunodeficiency virus (PLWH) require high rates of medication adherence to antiretroviral therapy (ART) for a successful treatment outcome. Understanding the factors associated with incomplete adherence among those receiving integrase strand transfer inhibitor-containing single-tablet regimens (INSTI-STRs) is crucial for improving treatment outcomes. This study aimed to identify the factors contributing to incomplete ART adherence among Japanese PLWH receiving INSTI-STRs. Methods This multicenter cross-sectional study was conducted at 11 Japanese institutions as an anonymous survey. ART adherence was assessed using a self-reported questionnaire. We defined incomplete ART adherence as missing ≥ 1 dose of antiretroviral drugs (ARVs) over the past month. The factors associated with incomplete ART adherence were assessed using logistic regression analysis. Additionally, we investigated the associations between patients' satisfaction score with and need for ARVs and their adherence to ART. Results The final analysis included data of 387 patients who were treated with INSTI-STRs. Multivariate logistic regression demonstrated significant association of younger age (adjusted odds ratio [aOR], 0.79; 95%confidence interval [CI]: 0.64-0.99 for each 10-year increment) with incomplete ART adherence. Additionally, female sex (aOR, 3.98; 95%CI: 1.36-11.60); depressive symptoms (mild depression: aOR, 1.68; 95%CI: 1.001-2.82, moderate depression: aOR, 2.98; 95%CI: 1.35-6.53, and severe depression: aOR, 8.73; 95%CI: 1.38-55.00 vs. minimal depression); were also significantly associated with incomplete ART adherence when compared with the reference categories. Concomitant medication usage was significantly associated with a lower rate of incomplete ART adherence (1-4 medications: aOR, 0.53; 95%CI: 0.31-0.89 and ≥ 5 medications: aOR, 0.30; 95%CI: 0.13-0.70 vs. no concomitant medication usage). In the incomplete ART adherence group, satisfaction scores for various aspects were significantly lower. Furthermore, a lower proportion of patients in the incomplete ART adherence group preferred the option of "taking tablets daily and visiting the hospital every 3 months," compared to those in the complete ART adherence group (p = 0.008). Conclusions This study demonstrated that factors associated with incomplete ART adherence include younger age, female sex, no concomitant medication, and depressive symptoms. Despite ART simplification, incomplete adherence among PLWH receiving INSTI-STRs, remains a challenge, requiring additional actions.